Pengaruh Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Produk Pada Toko Anjani Frozen Food Legok – Tangerang - Annisa Hernawanti; Iis Noviyanti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the effect of Service Quality and Price both partially and simultaneously on Purchasing Decisions at Anjani Frozen Food Legok Tangerang Store with a sample of 99 respondents. The method used is a quantitative method with an associative approach. The data analysis used in this study is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, T test and F test. The results of this study are Service Quality has a significant effect on Purchasing Decisions. Price has a significant effect on Purchasing Decisions. Service Quality and Price simultaneously have a significant effect on Purchasing Decisions. The test results on the first hypothesis obtained tcount> ttable or (8.563> 1.660). Based on the results of testing the second hypothesis, the value of t count> t table or (11.501> 1.660). Based on the results of testing the third hypothesis, the Fcount value is 75.852> Ftable 3.091. This shows that simultaneously the variables of Service Quality and Price have a significant influence on Purchasing Decisions.